2020
DOI: 10.1177/0194599820931803
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Smoking on Survival Outcomes in HPV‐Related Oropharyngeal Carcinoma: A Meta‐analysis

Abstract: Objective Characterize the survival impact of smoking on HPV-related (human papillomavirus) oropharyngeal squamous cell carcinoma. Data Sources Articles from 2000 to 2019 in the PubMed, Embase, and Cochrane Library databases were systematically reviewed for content and inclusion/exclusion criteria. Review Methods Two reviewers independently analyzed the databases for eligibility and quality of the articles. Demographic data, smoking history, and survival outcomes were recorded. Hazard ratios and 95% CIs were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
8
3
Order By: Relevance
“…Contrary to the above systematic reviews, 13,14 our data did not reflect a negative impact of smoking on survival in early stage disease which may be due to our single study having insufficient numbers in each group. The impact of smoking on survival may also be more pronounced in advanced stage disease, potentially from reduced efficacy of overall treatment previously described including radiotherapy resistance 14 . Ference et al also concluded that smoking increased disease progression in HPV positive OPC 14 …”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to the above systematic reviews, 13,14 our data did not reflect a negative impact of smoking on survival in early stage disease which may be due to our single study having insufficient numbers in each group. The impact of smoking on survival may also be more pronounced in advanced stage disease, potentially from reduced efficacy of overall treatment previously described including radiotherapy resistance 14 . Ference et al also concluded that smoking increased disease progression in HPV positive OPC 14 …”
Section: Discussioncontrasting
confidence: 99%
“…Our results demonstrate the negative impact of smoking on survival in stage III HPV positive OPC; however, no difference was noted in early stage disease. Two meta‐analyses, one by Chen et al and the other by Ference et al, showed that smoking adversely impacts recurrence and survival rates in patients with HPV positive OPC regardless of stage 13,14 . Contrary to the above systematic reviews, 13,14 our data did not reflect a negative impact of smoking on survival in early stage disease which may be due to our single study having insufficient numbers in each group.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Another study identified Helicobacter pylori co-infection is common in OPSCC, perhaps more so than HPV [122]. We suspect that tobacco use may facilitate a similar environment, explaining why cigarette smoking is a negative prognostic factor, even in HPV positive cancers [123,124]. In order to understand how microbiome compositional shifts can affect the mucosal homeostasis, a few groups have reported in silico gene expression analysis of the oral microbiome and how it relates to HPV positive OPSCC [125][126][127].…”
Section: The Microbiome As a Primer For Inflammation And Hpv Mediated...mentioning
confidence: 99%